Internet of Things: An Applied Research on Automation for Lock Shield - Bento, Antonio Carlos (International Research Journal of Management, IT & Social Sciences, 2018)
This study presents results obtained in applied research, involving controller boards (Arduino), at the Nove de Julho higher education institution, in the courses of Computer Science in São Paulo. In 2018, focusing mainly on the positive and negative points presented by the statistical data of the public security office. The methodology used to obtain the data was experimental research based on results obtained in the newspaper Estadão of June 25, 2017. Every hour, a house is invaded in the State of São Paulo, according to data of the Public Security Secretariat, focusing mainly in the qualitative and quantitative results, seeking greater security for homes with tilting gates, avoiding fraud and cloning of locks. Creating new automation equipment, focused on security, its assembly is more complex and more structured than the simple control boards and controls for swing gates. Thus obtaining a safer drive with a high power against fraud, since the system is mounted on top of the controller boards (Arduino), this system achieved a higher degree of reliability than conventional systems.